Current Status of Nanoparticle-Based Imaging Agents for Early Diagnosis of Cancer and Atherosclerosis - Saravanakumar, Gurusamy; Kim, Kwangmeyung; Park, Jae Hyung; Rhee, Kyehan; Kwon, Ick Chan (AMER SCIENTIFIC PUBLISHERS, 2009)
Endothelium plays a vital role in various vascular functions, and its dysfunction is a key underlying process closely related to diverse array of diseases such as atherosclerosis and tumor. Therefore, early detection of endothelial dysfunction at the functional or molecular level is of high importance for effective therapy. Recent advances in nanotechnology and our understanding in cellular and molecular biology have provided various biomedical imaging modalities and nanosized multimodal imaging agents. Multimodal nanoparticles that encompass the targeting ligands and magnetic/optical imaging labels enable us to visualize the pathophysiological process of various diseases using multiple imaging techniques. To visualize the specific pathogenic process at the molecular level, the imaging probe needs to be surface-functionalized with specific affinity ligands such as monoclonal antibodies (mAb). Combining the functional imaging agents along with therapeutic drugs has great potential for effective early detection, accurate diagnosis, and treatment of disease. The current review will highlight the application of various nanoparticle-based imaging agents and their recent developments in diagnosing endothelium dysfunction with a special emphasis on atherosclerosis and cancer.
Keywords: SUPERPARAMAGNETIC IRON-OXIDE; ADHESION MOLECULE-1 EXPRESSION; IN-VIVO; MAGNETIC-RESONANCE; GOLD NANOPARTICLES; CONTRAST AGENT; QUANTUM DOTS; ENDOTHELIAL DYSFUNCTION; MULTIMODAL NANOPARTICLE; TARGETED NANOPARTICLES